PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT ROYAL CITRA ABADI TANGERANG - Astri Rahma Wulandari; Whina Ratnawati (Journal of Research and Publication Innovation, 2024)
The aim of this is to determine the influence of Work Discipline and Work Environment on employee performance, both partially and simultaneously at PT. Royal Citra Abadi Tangerang. This research method uses a descriptive method that is associative in nature. The data collection method used is a questionnaire. The sample used in this research was the result of saturated sampling, namely 80 respondents. Data analysis used the SPSS version 26 program. The analysis tecniques used were data instrument testing, classical assumption testing, regression analysis, correlation coefficient analysis, determination coefficient analysis and hypothesis testing. Based on the research results, Work Discipline (X1) and Work Environment (X2) multiple linear regression equation Y = 9.883 + 0.268 X1 + 0.497 X2. Simultaneous hypotesis testing (F test) obtained a calculated F value > F tabel (39,779 > 2,72). this was also reinforced by a significance value of 0.000 < 0.05, thus H3 was accepted, meaning that simultaneously there was a significant influence between Work Discipline (X1) and Work Environment (X2) on employee performance (Y). The coefficient of determination value has an influence of 50.8% while the remainder (100% - 50,8% = 49,2%) is influenced by other factors that were not carried out in the research.